Impact of professional interpreters on outcomes of hospitalized children from migrant and refugee families with low English proficiency: a systematic review protocol. - Boylen, Susan; Wilson, S.; Gill, Fenella; Cherian, Sarah; Dantas, Jaya (Joanna Briggs Institute, 2017)
Review question/objective: The overall objective is to identify, critically appraise and synthesize evidence on the impact of professional interpreters on outcomes for hospitalized children (aged 0-18 years) from migrant and refugee families with low English proficiency. More specifically, does the intervention of the use of a professional interpreter for migrant and refugee families with low English proficiency impact on: